A Review of Translational Magnetic Resonance Imaging in Human and Rodent Experimental Models of Small Vessel Disease - Michael S. Stringer; Hedok Lee; Mikko T. Huuskonen; Bradley J. MacIntosh; Rosalind Brown; Axel Montagne; Sarah Atwi; Joel Ramirez; Maurits A. Jansen; Ian Marshall; Sandra E. Black; Berislav V. Zlokovic; et al. (Translational Stroke Research, 2021)
Cerebral small vessel disease (SVD) is a major health burden, yet the pathophysiology remains poorly understood with no effective treatment. Since much of SVD develops silently and insidiously, non-invasive neuroimaging such as MRI is fundamental to detecting and understanding SVD in humans. Several relevant SVD rodent models are established for which MRI can monitor in vivo changes over time prior to histological examination. Here, we critically review the MRI methods pertaining to salient rodent models and evaluate synergies with human SVD MRI methods. We found few relevant publications, but argue there is considerable scope for greater use of MRI in rodent models, and opportunities for harmonisation of the rodent-human methods to increase the translational potential of models to understand SVD in humans. We summarise current MR techniques used in SVD research, provide recommendations and examples and highlight practicalities for use of MRI SVD imaging protocols in pre-selected, relevant rodent models.